Robotic Assist and Virtual Surgical Planning in Orthognathic Surgery - Abrishami, Mehdi; Pourabdolah, Fatemeh; Dalvandi, Behnaz; Dalvandi, Reza; Sarrafan, Negar; Noorizadeh, Sara; Etezadinia, Alireza; Negargar, Sahar (Galen Medical Journal, 2024)
Orthognathic surgery, critical for correcting jaw deformities and improving facial function and aesthetics, has undergone transformative changes with the introduction of robotic assistance and Virtual Surgical Planning (VSP). These technologies have revolutionized the field by enhancing precision, reducing operative times, and enabling more predictable surgical outcomes. Robotic systems, including the Da Vinci® and ROSA® platforms, provide sub-millimeter precision in osteotomies, while VSP enables comprehensive preoperative planning by integrating advanced 3D imaging and simulation techniques. Together, these technologies provide an unparalleled level of control and precision in surgical procedures, significantly enhancing patient outcomes. Major advancements in the field include the integration of artificial intelligence and machine learning into surgical planning, which allows for better prediction of postoperative outcomes and real-time adjustments during surgery. Augmented reality is also gaining traction as a tool for intraoperative guidance, further enhancing the precision of robotic-assisted procedures. Emerging technologies such as haptic feedback systems and next-generation robotic arms hold promise for even greater improvements in surgical accuracy and efficiency. The relevance of these technologies to clinical practice is profound. By reducing complications, enhancing accuracy, and improving both functional and aesthetic results, robotic assistance and VSP are redefining standards in orthognathic surgery. However, barriers related to cost, surgeon training, and infrastructure must be addressed to enable the widespread adoption of these technologies. Future research should focus on validating these technologies in large-scale clinical trials and assessing their long-term benefits and cost-effectiveness. Ultimately, the integration of these cutting-edge technologies has the potential to revolutionize orthognathic surgery, making it safer, more efficient, and more personalized for patients.